Generic power flow algorithm for bipolar DC microgrids based on Newton–Raphson method - Lee, Jin-Oh; Kim, Yun-Su; Jeon, Jin-Hong (International journal of electrical power & energy systems, 2022)
This paper proposes a generic power flow algorithm for bipolar DC microgrids based on the Newton–Raphson (NR) method. The bipolar DC microgrid has gained considerable attention for its effectiveness and reliability with regard to power supply. To date, however, power flow algorithms for bipolar DC networks have not been fully investigated and generalized, although power flow analysis is an essential tool, with diverse applications ranging from network design to real-time control. In this study, a current injection-based power flow algorithm is established that considers the grounding scheme and voltage control method of energy source. Six bus types are defined, depending on the grounding scheme and voltage control combination. The unknown pole voltages and equations to be iteratively solved are identified. Afterwards, the unknown pole voltages are updated via a single NR method, which makes the proposed method straightforward and efficient. The case study validates that the proposed power flow algorithm can find the bus voltages of each pole sufficiently close to the simulation results of PSCAD/EMTDC, while having a low computational burden. •Generic power flow algorithm for bipolar DC microgrids is proposed.•Proposed algorithm considers grounding schemes and control modes of energy sources.•Proposed algorithm aids various power system applications for bipolar DC microgrids.•Developed method has high accuracy and low computation time with single NR method.